Does baseline quality of life predict the occurrence of complications in resectable esophageal cancer?. (March 2022) - Sheng, Wei Gilis; Assogba, Emerline; Billa, Oumar; Meunier, Bernard; Gagnière, Johan; Collet, Denis; D'Journo, Xavier Benoît; Brigand, Cécile; Piessen, Guillaume; Dabakuyo-Yonli, Tienhan Sandrine
Abstract: Background: The aim of this study was to assess the impact of baseline health related quality of life (HRQOL) on the occurrence of postoperative complications and death in patients with resectable esophageal cancer. Methods: Existing data from a prospective, multicenter, open label, randomized, controlled phase III trial comparing hybrid versus open esophagectomy in patients with resectable esophageal cancer from 2009 to 2012 in France were used. A Cox regression model was used to assess the prognostic value of the baseline HRQOL score on the occurrence of major complications (MC), and major pulmonary complications (MPC) at 30 days post-surgery, as well as on 1-year postoperative overall survival (OS). Results: Every 10-point increase in the baseline role functioning score was associated with a 14% reduction in the risk of MC, while every 10-point increase in fatigue or pain score was associated with an 18% increase in the risk of MC. Similarly, higher scores on fatigue and pain were associated with a higher risk of MPC. Compared with the hybrid procedure, patients undergoing open esophagectomy had a significantly higher risk of MC and MPC. Patients diagnosed with esophageal adenocarcinoma were at significantly lower risk of MC or MPC compared to patients with esophageal squamous cell carcinoma. Higher pain (HR = 1.23, p = 0.035) and insomnia (HR = 1.16, P = 0.031) scores were associated with increased 1-year OS. Conclusion: Fatigue, pain, insomnia, and squamous cell pathology were indicators of poor prognosis, and that the presence of these findings might possibly change the management plan towards other forms of treatment and warrant close attention. Highlights: Quality of life predicts the postoperative complications in esophageal cancer patients. Baseline role functioning had a protective effect against complications. Fatigue and pain were the risk factors of postoperative complications. Squamous cell pathology, pain and insomnia were risk factors for 1-year OS.